Treatment Outcomes in Patients Treated With Galcanezumab vs Placebo: Post Hoc Analyses From a Phase 3 Randomized Study in Patients With Episodic Cluster Headache. Issue 10 (11th November 2020) - Kudrow, David; Andrews, J. Scott; Rettiganti, Mallikarjuna; Oakes, Tina; Bardos, Jennifer; Gaul, Charly; Riesenberg, Robert; Wenzel, Richard; Kuruppu, Dulanji; Martinez, James
Abstract : Background: Cluster headache (CH) is a highly disabling primary headache disorder. To date, characterization of outcomes in the preventive treatment of episodic CH, including precise definitions of clinically meaningful attack frequency reduction and impact on acute treatment management, is lacking. Methods: This was a Phase 3, randomized, double‐blind, placebo‐controlled study in patients (men or women aged 18‐65 years) diagnosed with episodic CH as defined by the International Classification of Headache Disorders‐3 beta criteria. In this post hoc analysis, we evaluated the median time‐to‐first occurrence of ≥50, ≥75, or 100% reduction from baseline in CH attack frequency, and impact on acute medication use. An anchor‐based assessment of clinically relevant attack frequency reduction using the Patient Global Impression of Improvement (PGI‐I) scores at Week 4 was also assessed. Results: The median time‐to‐first occurrence of ≥50, ≥75, or 100% reduction from baseline in CH attacks was consistently shorter (9‐10 days sooner) with galcanezumab vs placebo (median [95% confidence interval, 95% CI]: ≥50%, 5 days [4.0 to 7.0] vs 14 days [6.0 to 19.0]; ≥75%, 11 days [7.0 to 16.0] vs 21 days [13.0 to 26.0]; 100%, 22 days [16.0 to 37.0] vs 32 days [23.0 to 34.0]). Mean reduction from baseline in the overall frequency of weekly pooled acute medication use across Weeks 1‐3 was significantly greater with galcanezumab vs placebo (11.0 vs 5.5; odds ratio, OR [95% CI]: 5.52 [1.02, 10.01]; P value = .017). Patients reporting "much better" on the PGI‐I experienced a median weekly CH attack reduction of approximately 43% from baseline across Weeks 1‐3. The overall odds of achieving an attack reduction threshold of 43% across Weeks 1‐3 was significantly higher with galcanezumab vs placebo (Weeks 1‐3: OR [95% CI], 2.60 [1.3 to 5.3]). Conclusions: Faster median time‐to‐first occurrence of response rates, lower frequency of pooled acute medications use, and a greater proportion of patients achieving a response anchored by patient‐reported improvement were observed for galcanezumab vs placebo.